GENE THERAPY FOR MUCOPOLYSACCHARIDOSIS IIIB - HORDEAUX JULIETTE; WILSON JAMES; HINDERER CHRISTIAN (2020)
Provided herein is a recombinant AAV (rAAV) comprising an AAV capsid and a vector genome packaged therein, wherein the vector genome comprises an AAV 5' inverted terminal repeat (ITR), an engineered nucleic acid sequence encoding a functional human N-acetyl-alpha-glucosaminidase (hNAGLU), a regulatory sequence which direct expression of hNAGLU in a target cell, and an AAV 3 ' ITR. Also provided isa pharmaceutical composition comprising a rAAV as described herein in a formulation buffer, and a method of treating a human subject diagnosed with MPS IIIB. 本文提供一种包含AAV衣壳和包装在其中的载体基因组的重组AAV(rAAV)，其中所述载体基因组包含AAV5'反向末端重复序列(ITR)、编码功能性人类N-乙酰基-α-氨基葡萄糖苷酶(hNAGLU)的工程化核酸序列、指导hNAGLU在靶细胞中的表达的调控序列和AAV 3'ITR。还提供一种在制剂缓冲液中包含如本文描述的rAAV的药物组合物，以及治疗诊断患有MPS IIIB的人类受试者的方法。